Acute Toxicity Ethanol Extract of Bidara Leaves (Ziziphus spina-christi L.) Against Liver and Kidney Function of White Rats - Nur Syamsi Dhuha; Haeria; Hardyanti Eka Putri (HM Publisher, 2020)
Bidara plants have the efficacy as antioxidants, anti-inflammatory, antimicrobial, anti- fungal and prevents tumours. Bidara is efficacious to protect human DNA cells caused by damage from actinic radiation. This study aims to explore the acute toxicity test of the ethanol extract of Bidara leaves using white mice as experimental animals. A total of 30 white rats (Rattus norvegicus) Wistar strain obtained from the Eureka Research Laboratory (Palembang, Indonesia) weighing between 200 - 250 grams. After one week of adaptation, the mice were randomly divided into the following six groups, each containing five animals: Normal control group and Bidara extract group (50mg/kg BW; 150 mg/kg BW; 450 mg/kg BW; 1350 mg/kg BW; and 4050 mg/kg BW). This study shows that the extract of Bidara leaves has a relatively high toxic dose, namely at a dose of 4050 mg/kg BW. Bidara leaf extract at doses below 1500 mg/kg BW, shows no toxic effect on the liver. In conclusion, bidara leaf extract has a toxic dose above 4000 mg/kg BW in Wistar white rats.